Endocrine Surgery in Children (Springer Berlin Heidelberg, 2018)
This book provides in-depth practical advice on how to manage children with endocrine conditions that may benefit from surgery. It is more detailed than general pediatric surgery texts and more surgically oriented than endocrinology texts. The first section is devoted to the thyroid and parathyroid, with detailed discussion of thyroid nodules, thyroid cancer, hyperthyroidism, hyperparathyroidism, and multiple endocrine neoplasia. The second section on the pancreas focuses on nesidioblastosis, islet cell transplantation, the surgical treatment of diabetes, and surgical complications of diabetes. Adrenal disorders, including neuroblastoma, pheochromocytoma, and adrenal masses, are then discussed, followed by a section on the evaluation and management of ovarian and testicular torsion and tumors. The closing section addresses miscellaneous topics such as gynecomastia in boys and growth restriction surgery. This book will serve as an invaluable reference for all practitioners and trainees who care for children with endocrine problems for which surgery is considered.